2023
DOI: 10.1021/acsabm.2c00973
|View full text |Cite
|
Sign up to set email alerts
|

Drug Delivery Systems for Localized Cancer Combination Therapy

Abstract: With over 2 million cancer cases and over 600,000 cancer-associated deaths predicted in the U.S. for 2022, this life-debilitating disease continuously impacts the lives of people across the nation every day. Therapeutic treatment options for cancer have historically involved chemotherapies to eradicate tumors with cytotoxic mechanisms which can negatively affect the efficacy versus toxicity ratio of treatment. With a need for more directed and therapeutically active options, targeted small-molecule inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 139 publications
0
7
0
Order By: Relevance
“…68,69 Maximizing the efficacy of the treatment depends on the dose of drug that reaches the target site, so therapy is carried out at the target site through localized delivery platforms. 70 Local delivery systems have the ability to deliver high doses of therapeutic molecules at the target site and provide controlled and sustained drug molecule release with minimized nonspecific distribution of therapeutics in healthy tissues. 71,72 Hydrogel-based local drug delivery system is one of the long-acting drug delivery formulations that allow controlled drug release over days, weeks, months, and years after single-dose administration and a stable pharmacokinetic profile.…”
Section: Hydrogels For the Local Delivery Of Drugs For Tumor Metastas...mentioning
confidence: 99%
See 1 more Smart Citation
“…68,69 Maximizing the efficacy of the treatment depends on the dose of drug that reaches the target site, so therapy is carried out at the target site through localized delivery platforms. 70 Local delivery systems have the ability to deliver high doses of therapeutic molecules at the target site and provide controlled and sustained drug molecule release with minimized nonspecific distribution of therapeutics in healthy tissues. 71,72 Hydrogel-based local drug delivery system is one of the long-acting drug delivery formulations that allow controlled drug release over days, weeks, months, and years after single-dose administration and a stable pharmacokinetic profile.…”
Section: Hydrogels For the Local Delivery Of Drugs For Tumor Metastas...mentioning
confidence: 99%
“…Hydrogels are attractive for the controlled delivery of therapeutic agents such as chemotherapeutic drugs, immunosuppressive agents, antibodies, vaccines, cytokines, and immune cells. 70 Despite the interesting properties of hydrogels in drug delivery systems, some limitations still exist (Table 2). Because they are soft, hydrophilic, and wet materials, hydrogels are limited to encapsulating hydrophobic drugs and have relatively low tensile strengths.…”
Section: Hydrogels For the Local Delivery Of Drugs For Tumor Metastas...mentioning
confidence: 99%
“…The method of vaccine delivery is also a consideration in the development of cancer therapeutic vaccines [100][101][102]. The vast majority of vaccination trials in glioblastomas utilize subcutaneous, intradermal, or intravenous delivery methods (Table 1).…”
Section: Deliverymentioning
confidence: 99%
“…However, there is increasing interest in novel drug delivery methods that may improve efficacy. Some examples of local delivery include the following: polymeric wafers, nanofibrous scaffolds, and hydrogels [100][101][102]. While out of the scope of the present review, recent articles extensively review advances in drug delivery that may be incorporated into vaccine development for GBM [100][101][102].…”
Section: Deliverymentioning
confidence: 99%
“…For example, PROVENGE, an immune cell-based vaccine, has been approved by the US FDA to treat hormone-refractory prostate cancer ( Cheever and Higano, 2011 ). Studies have shown that storage conditions, formulation, stability in vivo , targeting, blood concentration, target concentration and other factors are important factors affecting the therapeutic effect of drugs ( Vitharana et al, 2023 ; Woodring et al, 2023 ). In the process of new drug research exploration, researchers have conducted more investigations for these factors and made great progress.…”
Section: Introductionmentioning
confidence: 99%